Successful treatment of metastatic uveal melanoma with ipilimumab and nivolumab after severe progression under tebentafusp: a case report - Reiter, Selina; Schroeder, Christopher; Broche, Julian; Sinnberg, Tobias; Bonzheim, Irina; Süsskind, Daniela; Flatz, Lukas; Forschner, Andrea (Frontiers in Oncology, 2023)
Metastatic uveal melanoma (UM) is a rare form of melanoma differing from cutaneous melanoma by etiology, prognosis, driver mutations, pattern of metastases and poor response rate to immune checkpoint inhibitors (ICI). Recently, a bispecific gp100 peptide-HLA-directed CD3 T cell engager, tebentafusp, has been approved for the treatment of HLA-A*02:01 metastatic or unresectable UM. While the treatment regime is complex with weekly administrations and close monitoring, the response rate is limited. Only a few data exist on combined ICI in UM after previous progression on tebentafusp. In this case report, we present a patient with metastatic UM who first suffered extensive progression under treatment with tebentafusp but in the following had an excellent response to combined ICI. We discuss possible interactions that could explain responsiveness to ICI after pretreatment with tebentafusp in advanced UM.